ABOUT “THE BOOK BULGARIAN LITERARY MODERNISM. THE PROBLEM OF TIME AND IDENTITY” - Alexandra Antonova (Издател)
Dr. Ivan Hristov’s book examines Bulgarian literary modernism in a series of relations – to native, female, media, socialist realism, totalitarian art, postmodernism – relations that set a characteristic mode of constantly returning rethinking, reperception of the modernism phenomena. Research develops the concepts as contexts and approaches, developing the possibilities of contextualization, challenging the limits of meaning. Modernism is thought outside of its traditional, narrower chronological setting, and is seen in development, thought its thinking about identity and time, captured in a string of key concepts.